2021
DOI: 10.1029/2020je006418
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Induction Responses of Jupiter's Ocean Moons Including Effects From Adiabatic Convection

Abstract: The jovian system is of particular interest for studying magnetic induction in icy ocean worlds. Jupiter has a strong magnetic field whose dipole axis is tilted 9.6° with respect to its rotation axis (Acuna & Ness, 1976), while the orbits of the Galilean moons lie very nearly in the equatorial plane of Jupiter. This means that Jupiter's magnetic field varies in time at the orbital positions of the satellites. Also, the outer layers of the

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(79 citation statements)
references
References 69 publications
2
62
0
Order By: Relevance
“…The physical meaning of the amplitude and phase parameters is that they represent the relative magnitude and phase delay or lag of the induced magnetic moment with respect to that which would be induced by a perfectly conducting sphere of radius M E R . For additional background, we refer the reader to the Supporting Information of Vance et al (2021), where it is shown that the complex response function…”
Section:  I K K Ementioning
confidence: 99%
“…The physical meaning of the amplitude and phase parameters is that they represent the relative magnitude and phase delay or lag of the induced magnetic moment with respect to that which would be induced by a perfectly conducting sphere of radius M E R . For additional background, we refer the reader to the Supporting Information of Vance et al (2021), where it is shown that the complex response function…”
Section:  I K K Ementioning
confidence: 99%
“…The imaginary part of the conductivity must be zero to obtain a steady-state solution for the inductive response, as we have assumed the oscillations are slow enough that displacement currents may be ignored. The assumption that the conductivity is uniform within each layer holds approximately for any planetary body with layers that are global in extent, although geophysical conditions changing with depth require a greater number of radial layers in order to be adequately represented ( Vance et al, 2021 ). The consequence of this assumption is that our model is not expected to be capable of predicting the induced field of a body containing localized melt lenses ( Schmidt et al, 2011 ), sills ( Michaut and Manga, 2014 ), etc.…”
Section: Methodsmentioning
confidence: 99%
“…For simplicity in deriving our model, we neglect movement of conducting material within the body (as in the case of ocean currents) and rotation of the body within the external field, each of which can induce secondary fields ( Saur et al, 2010 ; Vance et al, 2021 ). We also neglect currents outside the body.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the hypothesized Triton ocean, the icy Galilean moons possess subsurface oceans with conductances on the order of 𝐴𝐴 10 4 S, sustained by thermal contributions from accretional and radiogenic sources in addition to tidal heating-except for Callisto, which receives negligible tidal heat (see, e.g., Schilling et al, 2007;Seufert et al, 2011;Saur et al, 2015;Vance et al, 2021). Each of these moons displays strong inductive responses to the changing magnetic field of their ambient magnetospheric environments (e.g., Saur et al, 2010) which, outside of their conducting layers, are well-represented using a magnetic moment located at the center of each moon (e.g., Zimmer et al, 2000).…”
Section: Triton's Induced Magnetic Fieldmentioning
confidence: 99%